Emerging trends in distance running training: bridging science and empirical insights - a narrative review - Kelemen, B.; Benczenleitner, O.; Tóth, L. (International Journal of Sports Science & Coaching, 2025)
In recent years, distance running performances have undergone a radical improvement, attributed to multiple factors in the scientific literature. Alongside advancements in footwear, track, and nutritional supplement technologies, training methodologies have increasingly adopted scientific approaches and become widely accessible through online platforms. This narrative review aimed to explore recent trends in training innovations through a comprehensive review of the literature and a narrative analysis of training information shared by elite runners. The findings highlight two key advancements in distance running training: the emphasis on sub-threshold interval training (between LT1 and LT2) and the development of maximal sprinting speed (MSS), and therefore Anaerobic Speed Reserve (ASR). Sub-threshold intervals, monitored via lactate and heart rate, enable runners to perform substantial volumes of high-end aerobic work while avoiding overtraining by staying below the second lactate threshold. Additionally, incorporating brief, near-maximal sprints (>10 s) with full recovery improves Anaerobic Speed Reserve, enhancing runners` ability to sustain race pace with reduced effort. Recovery strategies, including alternating light and heavy training days, clustering sessions into double workouts, and employing periodization techniques such as increased polarization during the season, further optimize performance. The rapid and widespread accessibility of this knowledge through digital platforms may also contribute significantly to the contemporary advancements in distance running performances.